JUDICIAL OVERSIGHT IN THE PRE-TRIAL INVESTIGATION STAGE: A KEY MECHANISM FOR DEMOCRATIZING UZBEKISTAN'S CRIMINAL PROCEDURE - Tulaganova Gulchehra (Modern American Journals, 2026)
This article examines judicial oversight (court control) over the pre-trial investigation as one of the essential conditions for democratizing and modernizing Uzbekistan's judicial and legal system. It analyzes the introduction of court supervision during the pre-trial phase, its historical origins, objectives, and forms of implementation under the reformed Criminal Procedure Code. The study highlights how such oversight protects constitutional rights and freedoms, ensures the legality and validity of procedural actions, strengthens the adversarial principle, and enhances public trust in fair justice. Particular attention is given to the powers of investigative judges, the need to expand judicial authorization for certain investigative measures, and the role of court control in preventing procedural violations that could affect the quality of subsequent trial stages. The author argues that elevating judicial oversight to the level of a fundamental principle of criminal proceedings aligns Uzbekistan's legislation with international standards and contributes to broader societal democratization and modernization.
Keywords: Judicial oversight, pre-trial investigation, Criminal Procedure Code, investigative judge, constitutional rights, human rights protection, criminal proceedings stages, democratization of justice, adversarial principle, Uzbekistan judicial reforms